Pentahelix Analysis in the Development of Sundakerta Tourism Village, Tasikmalaya Regency, West Java Province : Analisis Pentahelix dalam Pengembangan Desa Wisata Sundakerta, Kab.Tasikmalaya, Prov.Jawa Barat - Perti Nur Alindi; Ardiyati (Jurnal Pemerintahan dan Politik, 2026)
Purpose: To analyze the application of the pentahelix model in developing Sundakerta Tourism Village, Tasikmalaya Regency, and identify its implementation challenges. Design/methodology/approach: Qualitative descriptive method through in-depth interviews, field observations, and documentation studies. Findings: Sundakerta's development involves pentahelix collaboration across Academic, Business, Government, Community, and Media elements. Natural, cultural, and religious potential supports local wisdom-based ecotourism, evidenced by the Arga Hot Springs. Key challenges include limited business capital, low product innovation, and suboptimal digital media utilization. Practical Implications: Recommends strengthening village governance, institutional capacity, and digital promotion strategies. Originality/Value: Enriches pentahelix and stakeholder theory literature in the context of ecotourism-based tourism village development. Research Type: Research Paper.